Analysis of the Prognosis and Related Factors for Patients With Stage IV Gestational Trophoblastic Neoplasia. Issue 3 (1st March 2014) - Yang, Junjun; Xiang, Yang; Wan, Xirun; Feng, Fengzhi; Ren, Tong
Abstract : Objective: This study aimed to investigate and analyze the treatments and prognoses of patients with stage IV gestational trophoblastic neoplasia (GTN). Methods: Between January 1990 and January 2010, 105 patients with stage IV GTN were treated in our hospital (Peking Union Medical College Hospital). A retrospective study is presented herein to report the prognoses of these patients and to statistically analyze the risk factors that affected the prognoses of patients with stage IV GTN. Results: After the treatments, of the 105 patients, 71 (67.6%) patients achieved complete remission, 15 (14.3%) patients exhibited partial remission, and 19 (18.1%) patients exhibited progression of the disease. In total, of the 105 patients, 30 (28.6%) patients died. Our statistical analyses have revealed that a previously failed multidrug chemotherapy history, multiorgan metastasis concomitant with renal metastasis, and surgical intervention all affected the prognoses of patients with stage IV GTN. In addition, patients with stage IV GTN with International Federation of Gynecology and Obstetrics scores below 12 were relatively more likely to obtain complete remission. Conclusions: Multidrug, multiroute chemotherapy, assisted by surgery when necessary, is the predominant strategy for patients with stage IV GTN. Fluorouracil-based multidrug chemotherapy can produce good outcomes for patients with stage IV GTN who were treated primarily. Adequate attention should be given to patients who have previously failed multidrug chemotherapy, have experienced multiorgan metastasis concomitant with renal metastasis, or have International Federation of Gynecology and Obstetrics scores of more than 12.